2009
DOI: 10.1186/1755-8794-2-33
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of gene expression in healthy individuals

Abstract: Background: The use of gene expression in venous blood either as a pharmacodynamic marker in clinical trials of drugs or as a diagnostic test requires knowledge of the variability in expression over time in healthy volunteers. Here we defined a normal range of gene expression over 6 months in the blood of four cohorts of healthy men and women who were stratified by age (22-55 years and > 55 years) and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…Similarly, progesterone treatment of murine peritoneal macrophages ex vivo enhanced the expression of MCP-1 and other cytokines following hydrogen peroxide exposure [21]. Differences in Kc/CXCL1 mRNA expression have also been reported among humans, where a study of whole blood from healthy volunteers found that women had a small but significant 1.3- to 1.5-fold increase in levels of Kc/CXCL1 mRNA compared to men [26]. The functional effects associated with higher mRNA levels may be limited in our study, however, as we did not observe significant differences between the genders for cytokine protein levels.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, progesterone treatment of murine peritoneal macrophages ex vivo enhanced the expression of MCP-1 and other cytokines following hydrogen peroxide exposure [21]. Differences in Kc/CXCL1 mRNA expression have also been reported among humans, where a study of whole blood from healthy volunteers found that women had a small but significant 1.3- to 1.5-fold increase in levels of Kc/CXCL1 mRNA compared to men [26]. The functional effects associated with higher mRNA levels may be limited in our study, however, as we did not observe significant differences between the genders for cytokine protein levels.…”
Section: Discussionmentioning
confidence: 85%
“…For this reason, we investigated further whether sexual dimorphism in MS was driven by sex-specific genes. Sexrelated gene expression differences are normally present in several tissues, including blood [28,29], but they have never been specifically monitored under disease. Using relaxed statistics to maximize the number of differences existing in blood between genders, about 10% of the filtered genes resulted sex-specific in the healthy population, while only 2% in MS subjects.…”
Section: Sexual Dimorphism In Msmentioning
confidence: 99%
“…This is the first evidence to suggest time-point and extraction variability in miR expression. Other transcriptomics studies have also found differences in RNA expression over the course of 1-day to several weeks (7,8) while longer time-points were inconclusive due to confounding of technical variability (10,11). …”
Section: Resultsmentioning
confidence: 99%
“…Several transcriptomic studies have shown limited fluctuation in blood RNAs when measured from healthy individuals over several weeks to months (711). The proportion of transcripts with high intra-individual variability was attributed to a small number of immunological genes (i.e., immunoglobulin) (9) or inseparable from technical variability due to poor experimental design (10,11). This evidence from transcriptomics suggests that there may be similarly small intra-individual variability for miR transcription, however, this has not been previously measured.…”
Section: Introductionmentioning
confidence: 99%